The Establishment and Decision-Making about Recycling Model of Waste Electronic Products under Governments Incentive - Nie, Ju Bin; Zhao, Wenping (International Journal of Supply Chain Management, 2017)
This paper studied the decision making problem of the closed-loop supply chain with recycling a remanufacturing based on the constraint of government.Considering the effort of the recycling part, an incentive function was designed among the government, manufacturers, and the third party; then a multi-echelon closed-loop supply chain model with remanufacturing based on the third party and manufacture recycling was established. The result suggests that the governments incentive has a positive effect on the behavior of recycling waste products, the greater the units incentive factors of the government, the higher the recycling rate, and it can be more able to motivate the manufacturer and the third partys recycling behavior.